Towards more robust ignition of inertial fusion targets - Lee, JJ; Ruskov, RT; Martin, HS; Hughes, S; von der Leyen, MW; Paddock, RW; Timmis, R; Ouatu, I; Feng, QS; Howard, S; Atonga, E; Aboushelbaya, R; et al. (AIP Publishing, 2023)
Following the 1.3 MJ fusion milestone at the National Ignition Facility, the further development of inertial confinement fusion, both as a source for future electricity generation and for high energy density physics applications, requires the development of more robust ignition concepts at current laser facility energy scales. This can potentially be achieved by auxiliary heating the hotspot of low convergence wetted foam implosions where hydrodynamic and parametric instabilities are minimised. This paper presents the first multi-dimensional Vlasov-Maxwell and particle-in-cell simulations to model this collisionless interaction, only recently made possible by access to the largest modern supercomputers. The key parameter of interest is the maximum fraction of energy that can be extracted from the electron beams into the hotspot plasma. The simulations indicate that significant coupling efficiencies are achieved over a wide range of beam parameters and spatial configurations. The implications for experimental tests on the National Ignition Facility are discussed.